Retinal tolerance to dyes. Issue 9 (19th August 2005) - Lüke, C; Lüke, M; Dietlein, T S; Hueber, A; Jordan, J; Sickel, W; Kirchhof, B
Abstract : Background: Dye solutions for intraoperative staining of epiretinal membranes and the internal limiting membrane improve the visualisation of these thin structures and facilitate their removal. In the present study the authors investigated the effects of indocyanine green 0.05%, trypan blue 0.15%, and patent blue 0.48% on bovine retinal function. Methods: Bovine retina preparations were perfused with a standard solution and the electroretinogram (ERG) was recorded repeatedly. After recording of stable ERG amplitudes the nutrient solution was substituted by one of the dye solutions. The duration of retinal exposure to a dye solution was varied between 10 seconds and 2 minutes. Thereupon, the preparation was reperfused with standard solution for at least 115 minutes. The percentage of b-wave reduction after exposition was calculated. Results: Reductions of the b-wave amplitude were found for each dye solution tested. The effects after application of patent blue and indocyanine green were completely reversible within the recovery time for an exposure period of 60 and 30 seconds, respectively. The application of trypan blue lead to a loss of the b-wave when the retina was exposed for 15 seconds or longer. This effect was only partly reversible within the recovery time. Conclusion: The ERG showed toxic effects of trypan blue after a short period of retinal exposure. The intraocular application of trypan blue should be limited to selected cases. However, intraocular application of indocyanine green and patent blue in a sufficient concentration and taking account of a short period of retinal exposure seems possible.